Mechanism of International Legal Protection to the Forced Migrants in the Conditions of War Conflict - A. Y. Yastrebova (Московский журнал международного права)
The basic international rules and principles to provide the protection to Refugees, Asylum-Seekers and Internally Displaced Persons in war conditions are analysed in the above article. Especially, the provision of IV Geneva Convention 1949 and two Additional Protocols 1977 to Geneva Convention is considered regarding forced migrants situation. Some legal approaches are proposed in order to define their status, measures of internment and the modern backgrounds of humanitarian treatment of civilians. The functions of UNHCR and ICRC to support the protected persons in the conditions of war conflict are examined. The doctrines connected with the implementation of universal Human Rights treaties become truly demanded in war period.